Association of N-Linked Glycoprotein Acetyls and Colorectal Cancer Incidence and Mortality. - Paulette D Chandler; Akintunde O Akinkuolie; Deirdre K Tobias; Patrick R Lawler; Chungying Li; M Vinayaga Moorthy; Lu Wang; Daniel A Duprez; David R Jacobs; Robert J Glynn; James Otvos; Margery A Connelly; et al. (PLoS ONE, 2016)
Acute phase proteins highlight the dynamic interaction between inflammation and oncogenesis. GlycA, a novel nuclear magnetic resonance (NMR) inflammatory marker that identifies primarily circulating N-acetyl glycan groups attached to acute phase proteins, may be a future CRC risk biomarker.We examined the association between GlycA and incident CRC and mortality in two prospective cohorts (N = 34,320); Discovery cohort: 27,495 participants from Women's Health Study (WHS); Replication cohort: 6,784 participants from Multi-Ethnic Study of Atherosclerosis (MESA). Multivariable Cox models were adjusted for clinical risk factors and compared GlycA to acute phase proteins (high-sensitivity C-reactive protein [hsCRP], fibrinogen, and soluble intercellular adhesion molecule-1 [sICAM-1]).In WHS (median follow-up 19 years, 337 cases, 103 deaths), adjusted HRs (95% CIs) per SD increment of GlycA for CRC incidence and mortality were 1.19 (1.06-1.35; p = 0.004) and 1.24 (1.00-1.55; p = 0.05), respectively. We replicated findings in MESA (median follow-up 11 years, 70 cases, 23 deaths); HRs (95% CIs) per SD of GlycA for CRC incidence and mortality were 1.32 (1.06-1.65; p = 0.01) and 1.54 (1.06-2.23; p = 0.02), respectively, adjusting for age, sex, and race. Pooled analysis, adjusted HR (95% CI) per SD of GlycA for CRC incidence and mortality was 1.26 (1.15-1.39; p = 1 x 10-6). Other acute phase proteins (hsCRP, fibrinogen, and sICAM-1) had weaker or no association with CRC incidence, while only fibrinogen and GlycA were associated with CRC mortality.The clinical utility of GlycA to personalize CRC therapies or prevention warrants further study.ClinicalTrials.gov: WHS NCT00000479, MESA NCT00005487.